Peran Teknologi dalam Meningkatkan Efisiensi Pengelolaan Sarana dan Prasarana Pendidikan - Asfiyah, Anisa Nur; Khorunnisa, Nifathia; Rustini, Tin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The utilization of technology in managing educational facilities and infrastructure can create a more modern, efficient, and productive learning experience. Integrating technology in the management of educational facilities and infrastructure can improve efficiency, effectiveness, and accuracy in asset and resource management in educational institutions. Therefore, the role of managers and stakeholders is crucial to the success of education provision, especially in providing facilities and infrastructure. The aim of this research is to discuss how to integrate technology systems in the management of educational facilities and infrastructure to improve the quality of modern education. In the digital era, information and communication technology becomes very important in improving the efficiency, effectiveness, and accuracy in resource management in educational institutions. This article also discusses various technologies that can be integrated into the management of educational facilities and infrastructure, their benefits, and implementation methods. The use of technology can help in managing the security, maintenance, and monitoring of the condition of educational facilities and infrastructure. Hopefully, this article can provide insights and inspiration for those involved in the management of educational facilities and infrastructure to continue innovating and improving the quality of education in Indonesia.